Orchid bees respond to landscape composition differently depending on the multiscale approach - Silva Carneiro, Lázaro da (2022)
Context: Multiscale approaches are essential for understanding ecological processes and detecting the scale of effect. However, nested multiscale approaches retain the effect of the landscape attributes from the smaller spatial scales into the larger ones. Thus, decoupling the nested scales can reveal detailed ecological responses to landscape context, but this multiscale approach is poorly explored. Objectives: We evaluated the scale of effect of the forest cover (%) and landscape heterogeneity on Euglossini bee communities combining coupled and decoupled multiscale approaches. Methods: The Euglossini males were sampled in forest patches from 15 landscapes within the Atlantic Forest, southeast Brazil. For simplicity, we defined that the coupled approaches represented the local scales and decoupled the regional scales. We decoupled the scales by cutting out the smaller scales inserted into larger ones. We estimated the relationship of the bee community attributes with forest cover (%) and landscape heterogeneity in local and regional scales using Generalized Linear Models. Results: We found a trend of positive effects of landscape heterogeneity on species richness for decoupled regional scales. Forest cover and landscape heterogeneity on coupled local scales positively affected the Euglossini species abundance. The scale of effect for Euglossini species abundance was on coupled local scales. Conclusions: Combining coupled and decoupled multiscale approaches was essential to determine the scale of effect of the landscape composition on bee communities. Therefore, it is crucial to measure the influence of the landscape context on biodiversity. Maintaining landscapes with larger forest cover and spatial heterogeneity is important for bee requirements.